Phenotypic and genotypic characterization of probiotic strains in the context of antimicrobial resistance - Kerek, Ádám; Palkovicsné Pézsa, Nikolett; Kaszab, Eszter; Jerzsele, Ákos; Farkas, Orsolya (Frontiers in Veterinary Science, 2025)
IntroductionAntimicrobial resistance (AMR) has emerged as a critical global public health concern, particularly with regard to microorganisms used as probiotics in both veterinary and human healthcare. The aim of this study was to characterize the phenotypic and genotypic resistance profiles of several industrially applied probiotic bacterial strains, with special emphasis on the presence of antimicrobial resistance genes (ARGs).MethodsFive strains, Enterococcus faecium, Bacillus licheniformis, Bacillus subtilis, Lactobacillus rhamnosus, and Pediococcus acidilactici were analyzed. Minimum inhibitory concentration (MIC) testing revealed resistance in multiple strains to clinically relevant antibiotics such as gentamicin, amoxicillin, tylosin, and florfenicol.ResultsWhole-genome sequencing identified 27 distinct ARGs, primarily associated with efflux pumps and target protection or modification mechanisms. The Bacillus licheniformis strain harbored the most diverse ARG profile, whereas no resistance genes were detected in Pediococcus acidilactici.DiscussionThese findings highlight the necessity of integrating phenotypic and genotypic assessments for the safe application of probiotic strains in animals and potentially human use.